Computational methods in Materials Science studies - SIFUNA, James; AMOLO, George; MANYALI, George (KABARAK UNIVERSITY, 2018)
Recent years have seen a great improvement in the field of density functional Theory (DFT) calculation of electronic structure and properties of crystalline materials. There are many reasons that explain the current successful application of DFT to materials science related problems: The super speed of computers, software improvements and theory advancement. Based on these three pillars, we the computing scientists were able to understand the ground state properties of cubic scandium triflouride (ScF3) and if need arises, we willalso be able to explore the immense realm of the virtual materials. Indeed, high-throughput techniques for the search of novel crystal structures and the determination of band structure traits have become very popular in the field of computational materials science. Despite these, many challenges are still being faced. Common to all computational materials scientists is the unquenchable thirst for higher speed and better accuracy in DFT calculations. This paper aims to present recent advances in the theory and computational methods in DFT calculation of materials as well as to highlight computational results on structural properties of cubic ScF3 in comparison to experimental and other theoretical studies. We employed DFT as implemented in the Quantum ESPRESSO computer code. The obtained lattice parameters of between 3.96Å to 4.06Å was in agreement with the experimental lattice parameter of 4.03Å.
FULL TEXT
Keywords: DFT, materials science, computational methods